Amelanotic metastatic dermal melanoma with an unknown primary: A double diagnostic dilemma - Himalina S Sangma; Singh Anshul; Dhingra Karishma; Misra Vatsala (Wolters Kluwer Medknow Publications, 2023)
Malignant melanoma is most lethal skin malignancy accounting for 4% of all cutaneous cancers. It is usually seen in sun exposed areas but can occur anywhere in the body involving mucosal surfaces and internal organs as well. Rarely cases can present with metastases as the first manifestation of the disease, sometimes with unknown primary. Dermal melanomas are rarer which characteristically show lack of epidermotropism and thus enter as a close differential of metastatic melanomas that are exclusively dermal based. Amelanotic melanomas pose diagnostic difficulty clinically as well as on histopathology as the absence of pigments may simulate soft tissue tumors. In our study, we report a case of an elderly female presenting with a mass on the leg since 1 year, which on histopathology looked like a malignant soft tissue tumor with mixed epithelioid and spindle cells but on immunohistochemistry, it turned out to be an amelanotic melanoma that was completely based in the dermis. Following this, extensive serial sectioning of the remaining tissue specimen was done and two foci of lymphovascular invasion were detected favoring a diagnosis of a metastatic melanoma rather than a dermal melanoma. No obvious primary was found even after thorough work up. We are presenting this case to throw light on the difficulties encountered by pathologists in diagnosing melanomas that show lack of melanin and epidermotropism, both are considered to be the most reliable features in clinching the diagnosis and how this tricky presentation should be worked up to render a correct report.